2015
DOI: 10.1007/s00244-015-0233-9
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology of Marine Mammals: New Developments and Opportunities

Abstract: It is widely recognized that marine mammals are exposed to a wide variety of pollutants, with a weight of evidence indicating impacts on their health. Since hundreds of new chemicals enter the global market every year, the methods, approaches and technologies used to characterize pollution levels or impacts are also in a constant state of flux. However, legal and ethical constraints often limit the type and extent of toxicological research being carried out in marine mammals. Nevertheless, new and emerging in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…In addition to the numerous pollutants already present in the biosphere, hundreds of new compounds with incomplete toxicity testing enter the consumer market and therefore the oceans every year; as a result a considerable information lag arises between the initial creation and use of these chemicals and the time at which researchers and advocates understand the extent to which they affect the health of individuals, populations, and ecosystems (Weijs and Zaccaroni, 2016). Exposure to multiple toxicants and/or EDCs often happens simultaneously and can severely impact organismal homeostasis and function, since these substances can exert additive or synergistic effects which could lead to decreased growth rates and deleterious effects on long-term functional population viability (Crews et al, 2003;Beck et al, 2013;Worm et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the numerous pollutants already present in the biosphere, hundreds of new compounds with incomplete toxicity testing enter the consumer market and therefore the oceans every year; as a result a considerable information lag arises between the initial creation and use of these chemicals and the time at which researchers and advocates understand the extent to which they affect the health of individuals, populations, and ecosystems (Weijs and Zaccaroni, 2016). Exposure to multiple toxicants and/or EDCs often happens simultaneously and can severely impact organismal homeostasis and function, since these substances can exert additive or synergistic effects which could lead to decreased growth rates and deleterious effects on long-term functional population viability (Crews et al, 2003;Beck et al, 2013;Worm et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Fossi et al. , and Marsili et al , developed in vitro methods to evaluate cytochrome P450 induction by POPs exposure in the fibroblasts of several cetacean species. Over the past few years, toxicological research using cetacean fibroblasts has attracted attention, as summarized in review articles on culturing methods and applications of the cells. , These studies have demonstrated that cultured cells derived from biopsy specimens are valuable tools for assessing the toxic effects and risks of environmental chemicals on cetaceans. However, only a few studies have cultured and utilized cells from stranded animals; , additionally, the effects of xenobiotics on cetacean cells, such as cytotoxicity, increased apoptosis, and reduced cell viability, have not been well investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Fossi et al 25,26 and Marsili et al 27,28 culturing methods and applications of the cells. 29,30 These studies have demonstrated that cultured cells derived from biopsy specimens are valuable tools for assessing the toxic effects and risks of environmental chemicals on cetaceans. However, only a few studies have cultured and utilized cells from stranded animals; 27,28 additionally, the effects of xenobiotics on cetacean cells, such as cytotoxicity, increased apoptosis, and reduced cell viability, have not been well investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Information and features related to toxicological effects of metals in marine mammals are limited [124,145] despite the ample literature regarding toxic metal studies in all marine mammal groups, forcing the extrapolation of terrestrial and human responses and health effects for comparison instead [124].…”
Section: Toxicological Considerationsmentioning
confidence: 99%